Saikosaponin D Alleviates DOX-induced Cardiac Injury In Vivo and In Vitro. Issue 4 (April 2022) - Zhang, Yan-Jing; Wu, Si-Si; Chen, Xue-Mei; Pi, Jin-Kui; Cheng, Yu-Fei; Zhang, Yi; Wang, Xiao-Jiao; Luo, Dan; Zhou, Jin-Han; Xu, Jia-Yi; Li, Xue; Wu, Zhuang; et al.
Abstract: As a highly efficient anticancer agent, doxorubicin (DOX) is used for treatment of various cancers, but DOX-induced oxidative damages contribute to a degenerative irreversible cardiac toxicity. Saikosaponin D (SSD), which is a triterpenoid saponin with many biological activities including anti-inflammatory effects and antioxidant properties, provides protection against pathologic cardiac remodeling and fibrosis. In the present study, we investigated the work of SSD for DOX-induced cardiotoxicity and the involved mechanisms. We observed that DOX injection induced cardiac injury and malfunction and decreased survival rate. Besides, DOX treatment increased lactate dehydrogenase leakage, cardiomyocyte apoptosis, and myocardium fibrosis and decreased the size of cardiomyocytes. Meanwhile, all the effects were notably attenuated by SSD treatment. In vitro, we found that 1 μM SSD could enhance the proliferation of H9c2 cells and inhibit DOX-induced apoptosis. It was found that the levels of malondialdehyde (MDA) and reactive oxygen species were significantly reduced by improving the activities of the endogenous antioxidative enzymes including catalase and glutathione peroxidase. Furthermore, SSD treatment could downregulate the DOX-induced p38 phosphorylation. Our results suggested that SSD efficiently protected the cardiomyocytes from DOX-induced cardiotoxicity by inhibiting the excessive oxidative stress via p38-MAPK (mitogen-activated protein kinase, MAPK) signaling pathway.